Analysis of the Output Impedance from Switched DC/DC Converters - Hansson, Gustav; uussalu, marcus (My University, 2014)
The PuLS is a product used at Ericsson AB for performance testing of switched DC/DC converters by applying pulse shaped current waveforms. In this thesis, the PuLS is redesigned to be able to measure output impedance of switched DC/DC converters by drawing a sinusoidally shaped current while measuring the output voltage ripple. Existing measurement methods are investigated, the theoretical output impedance of a buck converter is calculated and simulations of two buck converters are implemented. Output impedance measurements of two buck converters are done using the redesigned PuLS. The results are compared with an existing impedance measurement method as well as simulations of the buck converters. It is shown that the PuLS is able to measure the output impedance of switched DC/DC converters at frequencies up to 80 kHz with results close to both the simulation and the previously made measurements. At frequencies greater than 80 kHz, the PuLS measurements shows a greater impedance compared to the simulation and the previously made measurements. When measuring passive components it is shown that the PuLS can measure impedance in the frequency range of 0.5-500 kHz.
Keywords: Elektroteknik; Elkraftteknik; Electrical engineering; Electric power engineering